1993
DOI: 10.1002/cncr.2820710416
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific differences in the relationship between oral contraceptive use and breast cancer

Abstract: Background. Nearly all studies have suggested that the use of oral contraceptives (OC) is not associated with the aggregate risk of breast cancer diagnosed in women aged 20–54 years. Because of age‐specific differences in the breast cancer–parity relationship and because of age‐specific differences in other breast cancer risk factors, the Centers for Disease Control reexamined data from the Cancer and Steroid Hormone Study (CASH) to assess whether OC use has different effects on the risk of breast cancer at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
47
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 32 publications
5
47
0
Order By: Relevance
“…Analyzing younger and older women together could mask heterogeneity of effects due to age, since previous age-specific analyses of the association between oral contraceptive use and breast cancer (regardless of histologic type) have observed variation by age. 17,21,[23][24][25] Romieu et al 18 reported that there was little difference in the effect of oral contraceptive use among different breast cancer histologies, but the authors did not report the effect estimates for the different histologies. Newcomer et al 26 reported ORs of 1.2 (95% CI 5 0.9-1.6) for the association between oral contraceptive ever use and invasive lobular cancer and 1.0 (95% CI 5 0.9-1.1) for the association between oral contraceptive ever use and invasive ductal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing younger and older women together could mask heterogeneity of effects due to age, since previous age-specific analyses of the association between oral contraceptive use and breast cancer (regardless of histologic type) have observed variation by age. 17,21,[23][24][25] Romieu et al 18 reported that there was little difference in the effect of oral contraceptive use among different breast cancer histologies, but the authors did not report the effect estimates for the different histologies. Newcomer et al 26 reported ORs of 1.2 (95% CI 5 0.9-1.6) for the association between oral contraceptive ever use and invasive lobular cancer and 1.0 (95% CI 5 0.9-1.1) for the association between oral contraceptive ever use and invasive ductal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been consistently shown that oral contraceptive use is associated with an increased risk of breast cancer in young women, [12][13][14][15][16][17][18][19][20][21][22][23][24][25] but not older women. 21,[23][24][25] Recently, Newcomer et al 26 reported that current oral contraceptive use, recent use, and older age at first use are associated with an increased risk of invasive lobular breast cancer, but not invasive ductal breast cancer in a population of middleaged women, suggesting that oral contraceptives may have effects related to specific histologic subtypes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown a small risk increase for developing breast cancer in women using the OCP whilst other studies were unable to demonstrate a correlation (16)(17)(18)(19). Kahlenborn Women of higher socio-economic status are at higher risk for the development of breast cancer (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have demonstrated an association between oral contraceptive use and breast cancer when focusing on women diagnosed under the age of 45 and/or on young users (Pike et al, 1981;Meierik et al, 1986;McPherson et al, 1987;Kay and Hannaford, 1988;Miller et al, 1989;Olsson et al, 1989; UK National Case-Control Study Group, 1989; WHO Collaborative Study of Neoplasia and Steroid Contraceptives, 1990;Weinstein et al, 1991;Wingo et al, 1991;Rookus and van Leeuwen, 1994;Brinton et al, Received 22 March 1996Revised 15 July 1996A Accepted 25 July 1996 Correspondence to: L Tryggvad6ttir 1995). This may indicate effects in young users because women diagnosed under the age of 45 in recent years tend to belong to the birth cohorts exposed at a young age.…”
mentioning
confidence: 99%